Adjuvant therapy in resected non-small cell lung cancer: current status and perspectives - Robert Pirker (Holistic Integrative Oncology)
Abstract Adjuvant chemotherapy increases overall survival of patients with completely resected non-small cell lung cancer. Adjuvant therapy with immune checkpoint inhibitors and tyrosine kinase inhibitors have further improved outcome in selected patients. These therapeutic achievements are discussed in the present commentary.